Evaluation of Quality Management System by Implementing Quality Matrix in Residential Projects Using SPSS - Subramani, T; Arsath, M (International Journal of Engineering and Technology, 2018)
Currently number of projects is lagging due poor management in execution and implementation. To overcome these factors in our project we proposed to find out the best quality management system (QMS) in the Civil Engineering industry by practicing with seven existing and new execution to actualizing quality network in private projects by utilizing Planning and statistical analysis software. By collecting questionnaire based on QMS form the existing literature review and same has been utilized for analysing and investigation in project planning management software. From the analysis we conclude that quality management system will play vital role in customer satisfaction and time consuming have the positive and critical changes in the QMS for each and every project in the construction industry in the execution level.Â Â